Liquidity Choice: A Study of Theoretical and Empirical Mystery in Context of Pakistan - DR. NAVEED HUSSAIN SHAH; DR. MUHAMMAD ARIF; DR. MUHAMMAD ASAD KHAN; DR. MUHAMMAD FAIZAN MALIK (Journal of Business & Tourism, 2021)
Contextual difference and inclusion of demographics as independent as well as new dimension of Liquidity preferencemade the study unique and novel in its essence. Empirical result of the correlation matrix is showing aninsignificant correlation of liquidity preference with gender, age, education, experience, annual income, annual savings, occupation and location.Regression analysis depicts significant relationship of liquidity preferencewith Education and Savings given by t-values -2.129, 2.190 and p-values -0 .620, 0.029 respectively.Liquidity preference is showing an insignificant relationship with Gender, Age, Experience, Income and Occupation given by t-values 0.117, 0.076, -1.220, -0.708,-0.144 and p-values .009, 006,-.120,-.075 and -.011 respectively.